Associations between sleep habits and mental health status and suicidality in a longitudinal survey of monozygotic twin adolescents. (24th January 2014) - Matamura, Misato; Tochigi, Mamoru; Usami, Satoshi; Yonehara, Hiromi; Fukushima, Masako; Nishida, Atsushi; Togo, Fumiharu; Sasaki, Tsukasa
Summary Several epidemiological studies have indicated that there is a relationship between sleep habits, such as sleep duration, bedtime and bedtime regularity, and mental health status, including depression and anxiety in adolescents. However, it is still to be clarified whether the relationship is direct cause‐and‐effect or mediated by the influence of genetic and other traits, i.e. quasi‐correlation. To examine this issue, we conducted a twin study using a total of 314 data for monozygotic twins from a longitudinal survey of sleep habits and mental health status conducted in a unified junior and senior high school (grades 7–12), located in Tokyo, Japan. Three‐level hierarchical linear model analysis showed that both bedtime and sleep duration had significant associations with the Japanese version of the 12‐item General Health Questionnaire (GHQ‐12) score, suicidal thoughts and the experience of self‐harm behaviours when genetic factors and shared environmental factors, which were completely shared between co‐twins, were controlled for. These associations were statistically significant even after controlling for bedtime regularity, which was also associated significantly with the GHQ‐12 score. These suggest that the associations between sleep habits and mental health status were still statistically significant after controlling for the influence of genetic and shared environmental factors of twins, and that there may be a direct cause‐and‐effect in the relationship in adolescents. Thus, late bedtime and short sleep duration could predict subsequent development of depression and anxiety, including suicidal or self‐injury risk. This suggests that poor mental health status in adolescents might be improved by health education and intervention concerning sleep and lifestyle habits.